Wood density of dominant tree species from the semi-evergreen tropical forest of Calakmul, Mexico - Chan-Coba, Gabriel; De Jong, Bernardus Hendricus Jozeph; González-Valdivia, Noel Antonio; López-Hernández, Juan Carlos; Morales-Ruiz, Danilo Enrique; Venegas-Venegas, José Apolonio; Reyes-Sosa, Mariela; Aryal, Deb Raj (Ecosistemas y Recursos Agropecuarios, 2022)
Wood density is a fundamental parameter for the accurate estimation of tree biomass in forest ecosystems. The semi-evergreen forest of the Mexican southeast is characterized by the high diversity of trees, so that it is necessary to study the variations in wood density. The objective of the study was to determine the variation in wood density of the dominant species of the semi-evergreen forest and to generate regression models with wood diameter. We collected 3,260 wood samples of 23 species of three diameter categories (thick, medium, and thin). The volume of wood was measured with the fluid displacement technique and the dry mass was determined in an oven at 70 ºC for 72 hours. Wood density was calculated as the ratio of mass to volume. Wood density varied significantly between species, Gymnanthes lucida Sw., being the largest with 0.85 g/cm3, and Bursera simaruba (L.) Sarg, the smallest with 0.37 g/cm3. Regression analysis showed that 20 out of 23 species presented a positive relationship between wood density and diameter size. It was concluded that wood density varied by species and diameter size of the tree in these forest ecosystems. The results are useful for modeling the dynamics of tree biomass accumulation of primary and secondary forests that are constantly changing in their structure and species composition.